Educating renal nurses - inferior vena caval ultrasound for intravascular volume assessment - Steinwandel, U.; Gibson, N.; Towell-Barnard, M.; Rippey, J.; Rosman, Johan (2018)
Aim: Volume status of haemodialysis patients can be evaluated by trained doctors using ultrasound (US) of the inferior vena cava (IVC). To date, renal nurses have not been taught this skill. As part of a larger study exploring the use of US by renal nurses we developed an educational program to ensure that renal nurses received adequate US training to attain competence in IVC ultrasound (IVC-US). Methods: The educational program was divided into four parts. Initially a clinical US expert delivered the necessary theoretical and then practical components of the program. After this the nurse undertook a period of self-directed US practice (100 scans). During this period three formative reviews of the recorded scan clips with feedback occurred. Specific feedback covered US technique, image optimisation and acquisition and image interpretation. Finally, as a summative assessment the nurse performed and interpreted 60 scans on 10 dialysis patients. These scans were independently assessed for quality and the nurse interpretations reviewed for accuracy, prior to deeming the candidate competent to independently perform IVC-US. Findings: Ultrasound education involves knowledge and skill acquisition. Initial theoretical and practical education must be translated into competence through task repetition and targeted feedback. A staged educational program that involves these components is likely to be successful. The rate for US skill acquisition varies and a summative assessment ensuring competence prior to independent scanning is important. Conclusions: This four-step program demonstrated that it is feasible to educate a renal nurse in IVC-US for intravascular volume assessment.